Labour trafficking prosecution: what is not working in Spain? - Villacampa Estiarte, Carolina (Contemporary justice review, 2023)
Despite being one of the most prevalent manifestations of trafficking in human beings, labour exploitation still results in few convictions. Based on 33 interviews with 28 professionals from the criminal justice system and 5 from the field of labour, this paper analyses the obstacles these professionals face when approaching this crime in Spain as a case study of what may not be working in other Western European countries. The research results point to three types of barriers encountered when dealing with these cases: regulatory; institutional (both pretrial and extra-procedural and during the criminal proceedings themselves); and those related to professionals’ attitudes towards these cases. The difficulties that can be included in each of these areas are identified, and solutions are proposed to overcome them to make the criminal justice system’s response to this crime more effective.